Analisis Aktivitas Membaca Cerita Berbantu Wayang Literasi dalam Pengembangan Kemampuan Baca Tulis Siswa SDN Karangrejo 02 - Wibisono, Yudi Catur; Murniati, Ngurah Ayu Nyoman; Sumarmiyati, Sumarmiyati; Hayat, Muhammad Syaipul (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Reading literacy is an important factor that is starting to be taught in elementary school education. With reading literacy activities, students will have the habit of reading and will automatically add information and insight for students. Reading literacy activities will foster students' interest in the talents they want to explore so that they will explore information about the talents they want to master more deeply. Most of the learning process will rely on the ability and awareness of learners of reading literacy. Reading literacy habits that are instilled early on to learners greatly affect the level of success and the ability of individual learners to capture the information they receive. In this 21st century, most students are more interested in playing cellphones than reading, this cannot be separated from parenting and the development of a digital age, this also happens with students at SD Negeri Karangrejo 02 Semarang. Therefore, concrete steps are needed in order to increase students' literacy interest in reading and writing. This study aims to analyze story reading activities with the help of puppet characters to develop reading literacy of grade 1 students of SDN Karangrejo 02 Semarang obtained from learning practices carried out by researchers and participant learning activities. In this research activity, researchers used a qualitative approach, then presented descriptively. The data collection method uses observation, interview, and documentation techniques. The data collected will then be analyzed, and the data analysis is descriptive. The results of data analysis show that students' reading activities are quite optimal, because when reading children's stories are assisted by literacy Puppets.